#1**+1 **

√-9 + √-36

For √-9, apply the radical rule: √-9=√-1√-9

Apply imaginary number rule which is √-1=i

So √-9i

√9=3, so now we have 3i

Now for √-36, apply the radical rule first: √-36=√-1√36

(Imaginary number step) We have √-36i now.

√36=6

So we have 6i

We ended up with 3i+6i which is equal to 9i, and that's your answer.

RainbowPanda
Feb 22, 2018

#2**+5 **

First, we can apply the radical rule, to get \(\sqrt{-1}\sqrt{9}\) . Then we can apply the imaginary rule, to get \(\sqrt{9} i=3i\) . Doing the same thing with, \(\sqrt{-36}\), we get \(6i\) . So, \(3i+6i=\boxed{9i}\)

tertre
Feb 22, 2018